Ressignificando a família em contextos não-monogâmicos: práticas de cuidado e apoio - Silva, Jéssica Vieira da (2026)
This research investigated the processes of redefining the concept of family in three non monogamous groups. The analysis considered both digital and physical spaces focused on sociability and the construction of collective bonds. The study aimed to understand how participants conceive, negotiate, and reinterpret family, kinship ties, and care practices. Instead of positioning themselves as just another type of family among others, these communities frequently propose new ways of naming and understanding affective bonds, destabilizing normative parameters centered on monogamy, conjugality, and consanguinity. Based on Pierre Bourdieu's theory of social classification systems, the study seeks to understand how these subjects, as classifying agents, develop alternative symbolic references, questioning legal and cultural conventions and asserting other legitimate ways of living interpersonal relations and affective ties. The research also analyzed the role of friendships as a structural element of these relational webs, highlighting alternative forms of organization and care that challenge traditional family models. The study is supported by theoretical frameworks on family, kinship, care, and gender, allowing the investigation to be situated within a broader context of different relational arrangements and affective practices. To this end, ethnography was adopted as the research method, focusing on the observation of interactions within the groups and on interviews conducted with the organizers of these spaces, seeking to apprehend the practices, discourses, and daily negotiations that sustain these experiences and reveal new ways of signifying family and care.